Determinants of the Human Development Index (Case Study of 12 Districts in East Java) - Putri, Amalia Elena; Susilowati, Dwi (Jurnal Ekonomi Pembangunan, 2024)
All countries face human development problems. As indicated by the relatively low level of the HDI. The quality of human life is an important factor in the development process. Of the 38 cities/districts in East Java, 12 districts require attention because they are categorized as moderate HDI levels by 2022. Therefore, it is important to make efforts to improve the quality of human development during the development process. This study aims to examine the independent socio-economic variables of poverty, economic growth, sanitation, and clean water on the dependent variable, namely the human development index in 12 districts of East Java Province in 2015-2022. This research uses panel data with the best model selection, namely the fixed effect model, and the test criteria are set at an error rate of 5%. The analysis results in an Adj R-Square value of 93.79%, which indicates a strong correlation between variables. The remaining 6.21% can be attributed to other factors not included in the analysis. Specifically, the results of this study explain the variables that affect and do not affect the human development index.